Cross-border banking in the EU since the crisis: What is driving the great retrenchment? - Lorenz Emter; Marcel Tirpák; Martin Schmitz (European Central Bank (ECB), 2018)
This paper examines the drivers of the retrenchment in cross-border banking in the European Union (EU) since the global financial crisis, which stands out in international comparison as banks located in the euro area and in the rest of the EU reduced their cross-border claims by around 25%. Particularly striking is the sharp and sustained reduction in intra-EU claims, especially in the form of deleveraging from cross-border interbank loans. Examining a wide range of possible determinants, we identify high non-performing loans as an important impediment to cross-border lending after the crisis, highlighting the spillovers from national banking sector conditions across the EU. We also find evidence that prudential policies can entail spillovers via cross-border banking in the EU, albeit with heterogeneity across instruments in terms of direction, magnitude and significance. Our results do not point to a major role of newly introduced bank levies in explaining cross-border banking developments.
Keywords: F21; F30; F42; G15; G28; 330; cross-border banking; international capital flows; deleveraging; financial integration; prudential policies; regulation; bank levy